2003
DOI: 10.1023/a:1024422220163
|View full text |Cite
|
Sign up to set email alerts
|

Changes in religious beliefs following trauma

Abstract: Information processing theorists propose that traumatic events can lead to disruptions in the processing of information and to changes in beliefs. This study examined the relationships among trauma, posttraumatic stress disorder (PTSD), and religious beliefs. Participants included 120 individuals from community and clinical samples who participated in the DSM-IV Field Trial Study on PTSD. Results indicated that the PTSD group was more likely to report changes in religious beliefs following the first/only traum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
129
3
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(144 citation statements)
references
References 24 publications
11
129
3
1
Order By: Relevance
“…Those who view their spirituality, faith community, and/or Higher Power as sources of support, validation, and acceptance are more able to make healthy meanings and recover than those who don't. Those who view their spirituality, faith community, and/or Higher Power as sources of judgment, punishment, or rejection have difficulty recovering from trauma (Elliott, 1994;Falsetti, Resick, & Davis, 2003;Fitchett, Rybarczyk, Demarco, & Nicholas, 1999;Fontana & Rosenheck, 2004;Harris et al, 2008b;Pargament, Koenig, Tarakeshwar, & Hahn, 2004;Strawbridge et al, 1998). This research suggests that using spiritually integrated interventions could help trauma survivors to more effectively use their spiritual practices and beliefs to deal with trauma and thus foster recovery.…”
mentioning
confidence: 92%
“…Those who view their spirituality, faith community, and/or Higher Power as sources of support, validation, and acceptance are more able to make healthy meanings and recover than those who don't. Those who view their spirituality, faith community, and/or Higher Power as sources of judgment, punishment, or rejection have difficulty recovering from trauma (Elliott, 1994;Falsetti, Resick, & Davis, 2003;Fitchett, Rybarczyk, Demarco, & Nicholas, 1999;Fontana & Rosenheck, 2004;Harris et al, 2008b;Pargament, Koenig, Tarakeshwar, & Hahn, 2004;Strawbridge et al, 1998). This research suggests that using spiritually integrated interventions could help trauma survivors to more effectively use their spiritual practices and beliefs to deal with trauma and thus foster recovery.…”
mentioning
confidence: 92%
“…Some authors have qualitatively suggested that religious functioning helps survivors make meaning of traumatic experiences (Hall & Johnson, 2001;Wilson & Moran, 1998). Data-based studies have shown that some survivors find their religious functioning helpful in coping with trauma, but other survivors find it hurtful and seek to reduce religious involvement or abandon their faith after experiencing trauma (Elliott, 1994;Falsetti, Resick, & Davis, 2003;Fitchett, Rybarczyk, DeMarco, & Nicholas, 1999;Fontana & Rosenheck, 2004;Pargament, Koenig, Tarakeshwar, & Hahn, 2002;Pargament, Murray-Swank, Magyar, & Ano, 2004;Strawbridge, Shema, Cohen, Rogers, & Kaplan, 1998). At this point, the reasons that individuals have such different responses to religious functioning after trauma are unclear.…”
mentioning
confidence: 99%
“…One important way trauma disrupts emotional, psychological, and personality processes is by shattering assumptions about safety, power/control, self, and the world (Janof-Bulman, 1992). Religious assumptions also are likely to be disrupted as beliefs in a benevolent, omnipotent G-d may appear inconsistent with traumatization, and this often precipitates existential crisis (Cadell, Regehr, & Hemsworth, 2003;Falsetti et al, 2003). Survivors must make new meaning of their perceptions of their world at physical, interpersonal, and spiritual levels (Decker, 1993;Wilson & Moran, 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tout abus peut ralentir ou même bloquer le développement spirituel de la victime (Ganje-Fling et McCarthy 1996, 257), mais les abus sexuels sont sans doute parmi les plus nocifs quant au rapport à Dieu. En effet, la plupart des victimes d'abus sexuels souffrent du syndrome de stress posttraumatique (Herman 1992), dont les porteurs démontrent plus de changement dans leurs croyances religieuses que les victimes de traumatisme qui ne souffrent pas dudit syndrome, soit 48 % versus 30 % (Falsetti et al 2003). C'est que les abus sexuels ont le plus souvent lieu à répéti-tion, durant une période moyenne de cinq ans pour les relations incestueuses (Heary et Solomon 1986, 59), à une époque où se constituent la psyché et la foi de l'enfant.…”
Section: Les Victimes D'abus Sexuels Confrontées à La Souffrance Et àunclassified